CMLHS Trip to Beijing - Saharudin, Ramli (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
25 December 2010. Flying above, the scenic view of its town looks like a painting on a canvas. Like Kuala Lumpur, Beijing the capital city of China, is crammed with traffic especially during peak hours. From 15 to 20 December, a group of 30 CMLHS associates with families and friends headed by Mohd Iszuani Mohd Hassan, head of Department of Foreign Languages set out on an international educational for a six day and five night visit to Beijing.